ASSESSMENT OF YIELD LOSS DUE TO LEAF CURL VIRUS IN TOMATO - MADHUMITA MAITY,; POLY SAHA, (The Bioscan, 2018)
An experiment was conducted to assess the yield loss in tomato due to tomato leaf curl virus disease in the Gangetic plains of West Bengal for two consecutive seasons (2012 and 2013). A linear regression equation was developed to find out the relation between the two components, diseases severity and yield loss and the prediction equation was developed. Results revealed that loss in yield was 0.65 to 0.69 t ha-1 for every 1% increase in disease severity in the experimental years respectively. In another experiment, evaluation of four promising tomato genotypes Patharkuchi (susceptible), BSS 575, Ajeet 11 and ARTH 2104 were evaluated both under protected and unprotected conditions. Highest disease severity recorded in unprotected condition than the protected. Highest yield observed in ARTH 2104 followed by Ajeet 11. Yield loss was highest in AJEET 11 followed by ARTH 2104 and BSS 575 and lowest yield loss was recorded in Patharkuchi though disease severity recorded maximum in it. So it may be concluded that ARTH 2104 would be the most promising genotype to be cultivated in the Indo-Gangetic region followed by Ajeet 11, provided proper prophylactic measure should be followed from the beginning to keep the crops away from the disease.